Generalized Aggressive Periodontitis as a Risk Factor for Dental Implant Failure: A Systematic Review and Meta‐Analysis. Issue 10 (1st October 2014) - Monje, Alberto; Alcoforado, Gil; Padial‐Molina, Miguel; Suarez, Fernando; Lin, Guo‐Hao; Wang, Hom‐Lay
Abstract : Background: Dental implant placement is a widely used treatment that provides functional and esthetic resolution for patients suffering from tooth loss. However, the incidence of peri‐implant diseases has been rising recently. Periodontal diseases and peri‐implant diseases share many similarities. Hence, it is important to find out whether patients with aggressive periodontal disease possess a higher risk of developing peri‐implant diseases. The aim of this study is to study whether generalized aggressive periodontitis (GAgP) has similar survival rates (SRs) and marginal bone loss (MBL) when compared with patients with chronic periodontitis (CP) and/or healthy patients (HPs). Methods: An electronic literature search was conducted by one reviewer (AM) in several databases from 2000 to 2013, including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Oral Health Group Trials Register databases, for articles written in English up to November 2013. Human clinical trials, either prospective or retrospective, that compared implant SR and MBL in patients with a history of GAgP versus those with CP or HPs were included. Results: A total of six non‐randomized prospective clinical trials met the inclusion criteria. The results showed SRs of 83.3% to 100% (GAgP), 96.4% to 100% (CP), and 96.9% to 100% (HP) over a mean period of 48.01 ± 71.99 months, with an overall risk ratio of 0.96 (95% confidence interval [CI] = 0.91 to 1.01, P = 0.14, GAgP versus HP) and 0.94 (95% CI = 0.87 to 1.01, P = 0.09, GAgP versus CP). However, when the "failure rate" as studied outcome was examined, meta‐analysis presented an overall risk ratio of 4.00 for the comparison between patients with AgP and HPs and an overall risk ratio of 3.97 when compared with patients with CP. The MBL weighted mean difference for each subgroup was 0.15 mm (95% CI = 0.04 to 0.26, HP versus CP), −0.28 mm (95% CI = −0.36 to −0.19, HP versus GAgP), and −0.43 mm (95% CI = −0.53 to −0.33, CP versus GAgP) over a mean period of 30 ± 18 months. Conclusions: Implant placement in patients with a history of GAgP might be considered a viable option to restore oral function with survival outcomes similar to those found in both patients with CP and HPs. However, the risk ratio for failure in patients with AgP is significantly higher when compared with HPs (4.0) and those with CP (3.97).